Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

suppose x1, x2 be the roots of ax^2+bx+c=0 and x^3,x^4 be the roots of px^2+qx+r=0. (i) x1, x2 , 1/x3, 1/x4 are in AP then (b^2 -4ac)/(q^2 -4pr) is equal to??? (ii) If a,b,c are in GP as well as x1,x2,x3,x4 are in GP, then p,q,r are in?? (iii)If x1,x2,x3,x4 are in GP, then its common ratio is??

suppose x1, x2 be the roots of ax^2+bx+c=0 and x^3,x^4 be the roots of px^2+qx+r=0.


(i) x1, x2 , 1/x3, 1/x4 are in AP then (b^2 -4ac)/(q^2 -4pr) is equal to???


(ii) If a,b,c are in GP as well as x1,x2,x3,x4 are in GP, then p,q,r are in??


(iii)If x1,x2,x3,x4 are in GP, then its common ratio is??

Grade:

1 Answers

abc
12 Points
7 years ago
Kindly confirm on the roots of the second equation. I suppose it must be x₃, x₄ and not x³, x⁴ as mentioned. 
On this supposition, let me provide the solution for the first question. If it is OK, kindly give a feed back, basing on which let me give the solutions for the rest of questions. 

[Even it is not correct, kindly give me a feed back, so that I can delete my solution - there by avoiding unnecessary TD ratings. Thanks and kind of your feed back] 

Solution for question 1. 

i) Applying properties of roots of Q.E., 
x₁ + x₂ = -b/a and x₁*x₂ = c/a --------- (1) 
x₃ + x₄ = -q/p and x₃*x₄ = r/p ----------- (2) 

ii) Since, x₁, x₂, 1/x₃, 1/x₄ are in A.P., 
x₂ - x₁ = 1/x₄ - 1/x₃ [Definition of AP - Difference of successive terms remain same] 

==> x₂ - x₁ = (x₃ - x₄)/(x₃*x₄) 

Squaring both sides, (x₂ - x₁)² = (x₃ - x₄)²/(x₃*x₄)² 

Applying algebraic identity, (a - b)² = (a + b)² - 4ab to the above, 
(x₂ + x₁)² - 4x₁*x₂ = {(x₃ + x₄)² - 4x₃*x₄}/(x₃*x₄)² 

Substituting the values from equations (1) & (2) to the above, 
(b²/a²) - 4c/a = [(q²/p²) - 4r/p]/(r/p)² 

This simplifies as: (b² - 4ac)/a² = (q² - 4pr)/r² 

So, (b² - 4ac)/(q² - 4pr) = (a/r)²

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free